How (and why) to teach history of science? - Poupová, Jana (Scientia in educatione, 2019)
The study draws attention to the benefits of teaching history of science (HOS). It deals with the history of HOS education from its beginnings in England in the second half of the 19th century and its expansion during the post-war period till the end of the 20th century when HOS was taken into account in many European curriculum documents. The article enumerates the most important events connected with HOS education in the Czech Republic and summarizes arguments in favour of teaching HOS (e.g. better understanding of nature of science or its humanizing). It evaluates the teaching methods used in the past (e.g. reading and discussing case studies, biographies or original scientific papers). The article provides a detailed description of the advantages and disadvantages of the constructivist and instrumental way of teaching history of biology and encourages teachers to make use of the strong points of both approaches.